The large jaguar that lived in the past of México: A forgotten fossil - Ruiz Ramoni, Damián (2019)
In the 1970’s, Oswald Mooser delivered to the Instituto de Geología, Universidad Nacional Autónoma de México, a fossil jaw recovered from the Chapala region, Jalisco, that he identified as Panthera onca. The collection label indicates doubts about this taxonomic assignment; an issue that remains unsolved. The aim of this work is to study the taxonomy and biogeographic implications of this material. With this aim, morphological and morphometric comparisons were made using fossil and current feline specimens. Additionally, a review of the fossil record of Pa. onca in Mexico was carried out using the material deposited in collections and reported in the literature. Our results indicate that the jaw from Jalisco belongs to a large Pleistocene form of jaguar historically called Pa. onca augusta. With the present record, there is a total of 10 paleontological localities in México where fossil jaguar records have been reported. Curiously, only one of these locations matches with the current distribution of this feline in North America, the San Josecito Cave in Nuevo León. With this information, there is evidence to confirm that the range distribution of the jaguar has been reduced significantly since the Pleistocene to the present.